AD, Volume 34, n° 3 & 4, 2009 - Full Issue - journal system, (Africa Development, 2009)
Contents Wasted Citizenship? Reclaimers and the Privatised Expansion of the Public Sphere Melanie Samson .......................... 1 Faillite de l'État et administration de l'espace public politique par les «jeunes patriotes » en Côte d'Ivoire Alfred Babo .................................. 27 State Failure, Crisis of Governance and Disengagement from the State in Africa Mojeed Adekunle Animashaun ................... 47 L'institutionalisation des délibérations dans l'espace public au sein des cheffries Bamileke de l'Ouest-Cameroun André Tchoupie ..................................65 Religious Factors in the Nigerian Public Sphere: Burdens and Prospects Jacob Kehinde Ayantayo ....................... 93 L'Islam et la femme dans l'espace public au Niger Mahaman Alio Ill Mozambique: The Rise of a Micro Dual State Maria Paula Meneses & Boaventura de Sousa Santos ..........129 The Contribution of Women in Influencing Legislation and Policy Formulation and Implementation in Uganda (1995-2005) Elijah Dickens Mushemeza ............................ 167 Parlementaires debout : L'interface de l'opposition politique pendant la transition en République démocratique du Congo Hubert Kabungulu Ngoy-Kangoy ................207 Capitalist Globalisation and the Role of the International Community in Resource Conflicts in Africa Adekunle Amuwo ..................... 227 Book Review / Revue de livre Erik Reinert's How Rich Countries Got Rich and Why Poor Countries Stay Poor Lansana Keita ..................... 269